(untitled) (Global Journal of Human-Social Science, 2012)
Child rearing has become challenging during past years and great expectations are placed for parenthood Although the public upbringing has become professionalized and the day-care and school services are available in today s society parents have the main responsibility for rearing children How and into what should children be raised In this article good parenthood is paralleled with parental love As a result two valuable and demanding underlying contents of parental love are discussed in this article setting up safe boundaries and constructing good self-esteem as the core of good parenthood and parental love The perspective in this article is fundamentally positive parental love appreciates and cares about the child and does not abandon the child even when his her behavior causes disappointments and trouble